On the Determinants of Fiscal Non-Compliance : An Empirical Analysis of Spain's Regions - Delgado-Tellez, Mar (IMF Working Papers; Working Paper, 2017)
This paper proposes an empirical framework that distinguishes voluntary from involuntary compliance with fiscal deficit targets on the basis of economic, institutional, and political factors. The framework is applied to Spain's Autonomous Communities (regions) over the period 2002-2015. Fiscal noncompliance among Spain's regions has shown to be persistent. It increases with the size of growth forecast errors and the extent to which fiscal targets are tightened, factors not fully under the control of regional governments. Non-compliance also tends to increase during election years, when vertical fiscal imbalances accentuate, and market financing costs subside. Strong fiscal rules have not shown any significant impact in containing fiscal non-compliance. Reducing fiscal non-compliance in multilevel governance systems such as the one in Spain requires a comprehensive assessment of intergovernmental fiscal arrangements that looks beyond rules-based frameworks by ensuring enforcement procedures are politically credible.